2014
DOI: 10.6000/2292-2598.2014.02.02.7
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorders: Survey of Healthcare Providers after Continuing Education

Abstract: Fetal alcohol spectrum disorders (FASD) occur as a result of prenatal alcohol exposure and are commonly associated with intellectual disability. Maternal alcohol consumption affects fetal development resulting in numerous lifelong physical, mental, and neurobehavioral abnormalities. To promote prevention of prenatal alcohol exposure and intervention to mitigate alcohol's postnatal effects, the Centers for Disease Control and Prevention (CDC) provides continuing education to healthcare providers through their F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…We found that records of visits to some providers frequently failed to note even a qualitative assessment of philtrum appearance or palpebral fissures, with 54% of children containing reports about the philtrum, and palpebral fissure length described as short ranging from 18% to 38%. This is consistent with one post-training survey that found that even after training on assessing patients for FAS, many providers of care to high-risk patients reported that they were using growth charts to evaluate height/length and weight for age but did not use lip philtrum guides or palpebral fissure length measurements (Evans, Tenkku, Kennedy, Zoorob, & Rudeen, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…We found that records of visits to some providers frequently failed to note even a qualitative assessment of philtrum appearance or palpebral fissures, with 54% of children containing reports about the philtrum, and palpebral fissure length described as short ranging from 18% to 38%. This is consistent with one post-training survey that found that even after training on assessing patients for FAS, many providers of care to high-risk patients reported that they were using growth charts to evaluate height/length and weight for age but did not use lip philtrum guides or palpebral fissure length measurements (Evans, Tenkku, Kennedy, Zoorob, & Rudeen, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Alcohol drinking is not only detrimental to the health of women, it is also risky to both the fetus and newborns if drinking women are potential or lactating mothers. In the past, numerous studies have shown children to be vulnerable to a number of developmentthreatening teratogens such as alcohol, drugs, radiation and viruses during the critical period of conception or lactation (Jones, Smith, Ulleland & Streissguth, 1973;Evans, Tenkku, Kennedy, Zoorob & Rudeen, 2014;Chasnoff, 1988;Jacobson, Jacobson & Humphrey, 1990). This leads to the manifestation of several developmental disorders ranging from "quantifiable" physical defects to "unquantifiable" mental abnormalities.…”
Section: Alcohol During Pregnancy and Lactation: Bridging Discordant ...mentioning
confidence: 99%